Cortical neuroanatomical changes related to specific language impairments in primary progressive aphasia - Kang, Sung Hoon; Park, Yu Hyun; Shin, Jiho; Kim, Hang-Rai; Yun, Jihwan; Jang, Hyemin; Kim, Hee Jin; Koh, Seong-Beom; Na, Duk L.; Suh, Mee Kyung; Seo, Sang Won (Frontiers in Aging Neuroscience, 2022)
Objective: Language function test-specific neural substrates in Korean patients with primary progressive aphasia (PPA) might differ from those in other causes of dementia and English-speaking PPA patients. We investigated the correlation between language performance tests and cortical thickness to determine neural substrates in Korean patients with PPA. Methods: Ninety-six patients with PPA were recruited from the memory clinic. To acquire neural substrates, we performed linear regression using the scores of each language test as a predictor, cortical thickness as an outcome and age, sex, years of education, and intracranial volume as confounders. Results: Poor performance in each language function test was associated with lower cortical thickness in specific cortical regions: (1) object naming and the bilateral anterior to mid-portion of the lateral temporal and basal temporal regions; (2) semantic generative naming and the bilateral anterior to mid-portion of the lateral temporal and basal temporal regions; (3) phonemic generative naming and the left prefrontal and inferior parietal regions; and (4) comprehension and the left posterior portion of the superior and middle temporal regions. In particular, the neural substrates of the semantic generative naming test in PPA patients, left anterior to mid-portion of the lateral and basal temporal regions, quite differed from those in patients with other causes of dementia. Conclusions: Our findings provide a better understanding of the different pathomechanisms for language impairments among PPA patients from those with other causes of dementia. Keywords: Neural substrate, language function test, primary progressive aphasia, object naming, generative naming, comprehension, cortical atrophy.